The dynamics of informal role development within sport teams: A case study approach. (May 2020) - Kim, Jeemin; Coleman, Taylor; Godfrey, Michael; Vierimaa, Matthew; Eys, Mark
Abstract: Aim: Recent literature suggested that informal roles can naturally arise in sport teams and impact team functioning. This case study aimed to identify the key factors involved in informal role emergence in sport teams. Method: Data were collected from 27 players from one male and one female intercollegiate basketball team using multiple methods. Questionnaires were administered four times during the sport season (October–February) to assess athlete personality and informal role occupancy, and a regular season game for each team was video-recorded to objectively code athletes' behaviors. Qualitative interviews were conducted following the end of the season with coaches and athletes from one team. Role profiles were created for each athlete, which included the information regarding his/her personality, role occupancy, and behavior frequencies. The role profiles were then organized into different role categories (e.g ., task vs. social specialist ) based on similarities in role occupancy, and the patterns in personality and behavior frequencies were examined within and across the categories. Interview data were analyzed thematically to complement the role profiles. Results: Members who occupied both task- and social-oriented informal roles were more extraverted and active, and had longer tenure compared to those who occupied no informal roles. Members specializing in task-oriented roles displayed lower extraversion and varying degrees of activity, and a social specialist was more extraverted and active. Deviant members who occupied negative roles were first-year members. The interview results suggested various person-related and contextual factors that influenced informal role development. Conclusion: Informal role emergence is a complex process that occurs via an interaction of multiple factors. A conceptual framework is proposed, which offers several avenues for future research to continue to investigate role dynamics in groups. Highlights: An in-depth case study was conducted to examine informal role emergence. Data were collected using questionnaires, videos, and interviews. Informal role occupants (vs. non role-occupants) showed higher in-game activities. Experienced and extraverted athletes were more likely to occupy informal roles. Situational factors (e.g., role void) also influenced informal role occupancy.